Monitoring of effectiveness of some preventive measures against influenza - Masaryková, Lucia; Balázi, Tomás; Fulmeková, Magdaléna; Lehocká, L'ubica (Ceska a Slovenska farmacie, 2012)
In our study we dealt with the frequently occurring influenza virus that infects humans regardless of age or sex. The flu is not of importance only in health problems but also in the economic ones, such as the treatment costs and patients' ability to work. We focused particularly on the most effective preventive measure against the virus, which is vaccination and the risk groups that are the most vulnerable ones to the virus. One of the objectives of this research was to identify the advantages and disadvantages of vaccination against influenza and available risks of vaccination within a group of 390 patients. We studied a group of 195 vaccinated patients and we tried to determine the effect of the vaccines used in these patients, and to compare this group with the same number of unvaccinated patients. The goal of the research was to identify the advantages and disadvantages of the vaccination against influenza, and the potential risks resulting from the vaccination. Based on our results, we found out that out of 195 vaccinated patients, only 4% returned to the doctor with the flu. Unvaccinated patients, however, visited the doctor four times more frequently, regardless of age. The resulting morbidity ratios clearly showed the importance, effectiveness and safety of the vaccination not only in high-risk groups, but also in people that are "out-of-danger", because the current flu virus spreads by droplet infection very quickly. Appropriate education and increased awareness among the population in Slovakia could improve the general attitude towards the vaccination against influenza and the vaccination rate (Slovakia 12%) could raise to a percentage comparable to that of the EU countries (France 30%, England 32%, the Netherlands 28% and Germany 26%).
Keywords: dospělí; Humans; lidé středního věku; Middle Aged; Young Adult; Influenza Vaccines; Slovakia; chřipka lidská; mladý dospělý; Slovenská republika; Influenza, Human; mužské pohlaví; Adult; Adolescent; ženské pohlaví; lidé; mladiství; Aged; vakcíny proti chřipce; senioři; Male; Female